2016
DOI: 10.5796/electrochemistry.84.349
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Electrochemical Detection of Nereistoxin by Reductive Desorption from Au(111) and Au(100)

Abstract: Sensitive electrochemical detection of nereistoxin (NEX), a widely used insecticide, by reductive desorption is studied. NEX is adsorbed onto a gold single-crystal electrode via its disulfide group to form a self-assembled monolayer (SAM), which shows a reductive desorption peak in alkaline solution. The detection limit depended on the modification time and the crystallographic orientation of Au. When a Au(111) electrode was used as a substrate, the limit of detection was 10 nM. This limit was decreased to 1 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In our previous study, NRTs were adsorbed on a single-crystal Au surface and showed a unique reductive desorption behavior in 0.1 M KOH. 29 The reductive desorption wave was so characteristic that we could distinguish NRT from other thiolated aliphatic amines. The detection limit was as low as 1 nM using an Au(100) single crystal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, NRTs were adsorbed on a single-crystal Au surface and showed a unique reductive desorption behavior in 0.1 M KOH. 29 The reductive desorption wave was so characteristic that we could distinguish NRT from other thiolated aliphatic amines. The detection limit was as low as 1 nM using an Au(100) single crystal.…”
mentioning
confidence: 99%
“…Therefore, NRT adsorbs on the Au surface by Au–S bond formation. In our previous study, NRTs were adsorbed on a single-crystal Au surface and showed a unique reductive desorption behavior in 0.1 M KOH . The reductive desorption wave was so characteristic that we could distinguish NRT from other thiolated aliphatic amines.…”
mentioning
confidence: 99%